The young ninja Dia yang tak tersentuh maut Simon Higgins ; penerjemah, Aan ; penyunting, Perwira Leo S. ; ilustrasi, Wisnu. - HIGGINS, Simon; Aan; Leo S., Perwira; Wisnu (B-First, 2010)
ix, 316 hlm. ilus. 20 cm.